Olowalu review: Developing identity through translanguaging in a multilingual literary magazine - Kasula, Alex Josef (Colombian Applied Linguistics Journal, 2016)
With the current trends in our globalized society, there is a clear increase in multilingualism; however, the understanding of multilingual identity and policy towards education stays relatively the same. Recent investigation in multilingualism in the US has shed light on the positive impacts of alternating policy in language education with regard to a greater understanding of how translanguaging and identity impact the language learner and language learning policies (García & Wei, 2013). The following article describes the development of an online multilingual literary magazine, Olowalu Review, that aimed to provide English language learners in an English-only language policy with a space to translanguage. Thus, having the opportunity to develop and express their multilingual identities. Goals and the development of the magazine are described in terms relating to current multilingual theory. While the outcomes and findings reveal how Olowalu Review enabled multilinguals to foster and exercise multilingual identities and skills, raise multilingual awareness, and act as an important multilingual artifact through an analysis of written submissions and interviews with authors. Pedagogical implications are discussed to empower language teachers, learners, or artists to develop the same or similar project for their own local, national, or global community.